2009
DOI: 10.1007/s10661-009-0773-4
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbon contamination in stormwater detention pond sediments in coastal South Carolina

Abstract: The purpose of this study was to characterize the polycyclic aromatic hydrocarbon (PAH) contamination in the sediments of stormwater detention ponds in coastal South Carolina. Levels of the sum of PAH analytes were significantly higher in the sediments of commercial ponds compared to that of reference, golf course, low-density residential, and high-density residential ponds. Isomer ratio analysis suggested that the predominant source of PAHs were pyrogenic; however, many ponds had a PAH signature consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…Among these 16 PAHs, low molecule weight PAHs (e.g., 3-4 rings) exhibited relative the higher levels. Compared with the urban industrialized areas around the world (McCready et al 2000;Notar et al 2001;Doong and Lin 2004;Weinstein et al 2010;Chen et al 2012;Shang et al 2013), the concentrations of PAHs in Lingding Bay were comparable to the gulf of Triest in Italia. The level of PAHs in Guangzhou channel was similar with the Yangtze River, but less than South Carolina and Syndey harbor.…”
Section: Resultsmentioning
confidence: 85%
“…Among these 16 PAHs, low molecule weight PAHs (e.g., 3-4 rings) exhibited relative the higher levels. Compared with the urban industrialized areas around the world (McCready et al 2000;Notar et al 2001;Doong and Lin 2004;Weinstein et al 2010;Chen et al 2012;Shang et al 2013), the concentrations of PAHs in Lingding Bay were comparable to the gulf of Triest in Italia. The level of PAHs in Guangzhou channel was similar with the Yangtze River, but less than South Carolina and Syndey harbor.…”
Section: Resultsmentioning
confidence: 85%
“…We recently characterized the chemical contaminants in the sediments of a variety of suburban stormwater detention ponds in coastal South Carolina (USA) [5,15,16]. Our results demonstrate that the sediments of stormwater ponds surrounded by commercial development had significantly elevated levels of polycyclic aromatic hydrocarbons (PAHs) compared to those ponds surrounded by golf courses, low density residential development, and high density residential development.…”
Section: Introductionmentioning
confidence: 94%
“…Sediment data were compiled from two recent studies [5,15]. One study surveyed PAH sediment contamination in 16 stormwater detention ponds and two reference ponds in the coastal counties [5].…”
Section: Pond Selection and Physical Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The industries located in the surrounding areas of the Meiliang Bay are primarily composed of machine shops, paper mills, textile mill, chemical plant, leather industries, power plants, and other manufacturers, all of which contributed to the levels of PAHs in Meiliang Bay. Weinstein et al (2010) also found that there was a significant positive relationship between drainage area and the level of PAHs concentration. Overall, the presence of PAHs in Meiliang Bay of Lake Taihu indicated the primary contaminant sources were incompletely treated or untreated industrial and municipal effluents, as well as agricultural runoff from surrounding areas, together with riverine water containing industrial and municipal sewage.…”
Section: Probabilistic Distributions Of Hazard Quotientsmentioning
confidence: 73%